Design, synthesis and biological evaluation of N, N-3-phenyl-3-benzylaminopropanamide derivatives as novel cholesteryl ester transfer protein inhibitor. Issue 8 (15th April 2016) - Zhao, Dongmei; Xie, Honglei; Bai, Changlin; Liu, Chunchi; Hao, Chenzhou; Zhao, Shizhen; Yuan, Hongli; Luo, Changqun; Wang, Jian; Lin, Bin; Zheng, Jiang; Cheng, Maosheng
Graphical abstract: Abstract: A series of N, N -3-phenyl-3-benzylaminopropanamide derivatives were identified as novel CETP (cholesteryl ester transfer protein) inhibitors. In our previous study, lead compoundL10 was discovered by pharmacophore-based virtual screening (Dong-Mei Zhao et al., 2014). Based onL10 (IC50 8.06 μM), compoundHL6 (IC50 10.7 μM) was discovered following systematic structure variation and biological tests. Further optimization of the structure–activity relationship (SAR) resulted in N, N -3-phenyl-3-benzylaminopro panamides derivatives as novel CETP inhibitors. They were synthesized and evaluated against CETP by BODIPY-CE fluorescence assay. Among them, HL16 (IC50 0.69 μM) was a highly potent CETP inhibitor in vitro. In addition, HL16 exhibited favorable HDL-C enhancement and LDL-C reduction in vivo by hamster. The molecular docking ofHL16 into the CETP was performed. The binding mode demonstrated thatHL16 occupied the CETP binding site and formed interactions with the key amino acid residues.